Efficacy of Some Plant Extracts against Root Rot Disease of Green Oak Lettuce (Lactuca sativa var. Crispa) Caused by Pythium sp. Grown in a Hydroponic System - Chaudhary, Lakshya Bahadur; Meetum, Pimjai; Kanjanamaneesathian, Mana; Adhikari, Roshan; Mongkol, Rachsawan (Journal of Agriculture and Environment, 2023)
An antifungal activity of the twelve plant extracts were tested against Pythium sp., the causal agents of root rot diseases grown in hydroponic systems. The crude extracts of Acorus calamus and Syzygium aromaticum completely inhibited the mycelial growth of Pythium sp. in the in vitro condition at 5,000 ppm, whilst Curcuma zedoaria and other plant extracts had show lesser inhibitory activity. Out of these twelve plant extracts selecting A. calamus, S. aromaticum and C. zedoaria for further in vivo test in nursery raising seedling in plastic tray of hydroponic system by inoculating Pythium sp. mycelial developed on agar medium, A. calamus rhizome extract exhibited highest inhibitory effect against % root tip colonized by Pythium sp. of 5.85 to 48 followed by S. aromaticum floral bud 9.97 to 60 and rhizome of C. zedoaria extract 28.32 to 90 at 2000 ppm on seven and twenty one days after inoculation respectively. The concentrations and application methods of these extracts should be further investigated to control the root rot disease of lettuce in the hydroponic system.